1993
DOI: 10.1139/g93-141
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial genome of Anopheles quadrimaculatus species A: complete nucleotide sequence and gene organization

Abstract: The complete sequence (15,455 bp) of the mitochondrial DNA of the mosquito Anopheles quadrimaculatus species A is reported. This genome is compact and very A+T rich (77.4% A+T). It contains genes for 2 ribosomal RNAs (rRNAs), 22 transfer RNAs (tRNAs), and 13 subunits of the mitochondrial inner membrane respiratory complexes. The gene arrangement is the same as in Drosophila yakuba, except that the positions of two contiguous tRNAs are reversed and a third tRNA is transcribed from the complementary strand. Prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
96
0
3

Year Published

1995
1995
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(118 citation statements)
references
References 0 publications
19
96
0
3
Order By: Relevance
“…As with other insect mtDNA studied to date (21)(22)(23)(24), the base composition of sequences in this study was strongly biased toward adenine and thymine, which comprised 72% of the total. The observed transition and transversion rates were comparable to those reported for other insect groups and the rate of transversions was significantly greater than that of transitions.…”
Section: Resultsmentioning
confidence: 52%
“…As with other insect mtDNA studied to date (21)(22)(23)(24), the base composition of sequences in this study was strongly biased toward adenine and thymine, which comprised 72% of the total. The observed transition and transversion rates were comparable to those reported for other insect groups and the rate of transversions was significantly greater than that of transitions.…”
Section: Resultsmentioning
confidence: 52%
“…Four amino acids in the Cterminal part of COII are believed to play this role: His-161, , and His-204 of the bovine protein sequence (Millett et al 1983;Capaldi 1990). Interestingly, the same four residues are conserved in Collembola, a snail (Lecanidou et al 1994), several primates (Adkins and Honeycutt 1994), and all pterygote insects studied to date (Liu and Beckenbach 1992;Willis et al 1992;Beckenbach et al 1993;Mitchell et al 1993;Sperling et al , 1995. In bacterial COII (Iwata et al 1995), the same residues participate in the formation of the copper center.…”
Section: Functional Aspects Of Amino Acid Conservationmentioning
confidence: 95%
“…Thaumanura had TTC (phenylalanine) in the corresponding position, but had a TAA terminator three codons upstream and another TAG terminator five codons downstream. In all these cases, however, the presence of a T, coupled with polyadenylation (Anderson et al 1981;Clayton 1984), might be enough to mark the termination of the gene as observed in the mitochondrial genome of other insects (Clary and Wolstenholme 1985;Liu and Beckenbach 1992;Crozier and Crozier 1993;Mitchell et al 1993) as well as in mammalian mitochondrial genes (Bibb et al 1981;Andersone et al 1982).…”
Section: Codon Usagementioning
confidence: 99%
“…For the P. sulpitia COI gene, no typical ATN initiator was found in its starting region or in its neighboring trnY sequences. As for the cox1 initiation codon in animals, significantly different cases have been reported, for example, tetranucleotides such as TTAG in Coreana raphaelis (Kim et al, 2006), ATAA in Drosophila yakuba (Clary & Wolstenholme, 1985) are used, while hexanucleotides such as TATTAG in Ostrinia nubilalis and Ostrinia furnicalis (Coates et al, 2005), TTTTAG in Bombyx mori (Yukuhiro et al, 2002), TATCTA in Penaeus monodon (Wilson et al, 2000), ATTTAA in Anopheles gambiae (Beard et al, 1993), Anopheles quadrimaculatus (Mitchell et al, 1993), and Ceratitis capitata (Spanos et al, 2000) are used. Generally, the trinucleotide TTG was assumed to be the cox1 start codon for some invertebrate taxa including insect species, such as Pyrocoelia rufa (Bae et al, 2004), Caligula boisdnvalii (Hong et al, 2008), and Acraea issoria .…”
Section: Protein-coding Genesmentioning
confidence: 99%